Perspectives of high-risk pregnant women on home care program in high-risk pregnancies: A multicenter, qualitative study - Masoumeh Sayahi; Shahrbanoo Salehin; Mehrnoosh Zakerkish; Afsaneh Keramat; Shahrbanoo Goli (Asian Pacific Journal of Reproduction)
Objective: To explore the perspectives of high-risk pregnant women regarding the home care program for high-risk pregnancies. Methods: This qualitative study was conducted in a university hospital and 5 comprehensive health centers in Ahvaz, Iran, from February 2023 to July 2023. The sampling method used was purposive sampling considering the maximum possible diversity, which continued until data saturation. 11 in-depth and semi-structured interviews were conducted with high-risk pregnant women. Data were simultaneously analysed using Graneheim and Lundman content analysis by MAXQDA version 20 software. Results: Data analysis extracted 3 themes, 12 categories, and 26 subcategories. The themes and categories were “high-risk pregnancy and related issues (pursuing treatment and paying attention to the high-risk situation by pregnant women, psychological aspect of high-risk pregnancy on pregnant women and caregivers, emotional and physical aspects of high-risk pregnancy, the consequences of high-risk pregnancy on the people around them and empowerment of high-risk pregnant women)”, “support dimension (family and community support for high-risk pregnant women)”, and “framework of program (acculturalization, means and equipment, security, manpower and the necessary arrangements for the home care)”. Conclusions: High-risk pregnancy affects various aspects of the lives of high-risk pregnant women and their families. Creating the necessary conditions for providing care at home plays a vital role in supporting high-risk pregnant women and removing related obstacles to receiving prenatal care in person. It will be especially beneficial for high-risk pregnant women in low-income areas.